PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE (TTW) BERBANTUAN MEDIA FLIPBOOK PADIKU TERHADAP KETERAMPILAN MENULIS SISWA KELAS V SD - Fatihatin, Dian Azizatul; Fakhriyah, Fina; Kironoratri, Lintang (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this study is to describe the effect of the Think Talk Write (TTW) learning model by Padiku flipbook media on the writing skills of fifth-grade students. This research applied a pre-experimental design with a one-group pretest-posttest method. The population of the study consists of all 18 fifth-grade students at SD 2 Hadipolo, using a saturated sampling technique. The results of the study indicate that there is an effect of the TTW learning model supported by Padiku flipbook media, as shown by the Paired Sample T-Test results with a Sig(2-tailed) value of 0.000 < 0.05. Thus, it can be concluded that the use of the TTW learning model, supported by the Padiku flipbook media, has a significant impact on students' writing skills. Student responses to the use of the TTW learning model with the Padiku flipbook media indicate that it made learning more active, enjoyable, engaging, and facilitated students' understanding of the material being taught.